Young women and men: Imagined futures of work and family formation in Australia. (December 2019) - Hill, Elizabeth; Baird, Marian; Vromen, Ariadne; Cooper, Rae; Meers, Zoe; Probyn, Elspeth
In the debates about the future of work there is a lack of analysis on how young women and men are approaching their future work and family lives. In this article we use data collected in the Australian Women's Working Future (AWWF) Project 2017 to analyse what young workers imagine will be important to their future success in work and family. We find that formal workplace supports for care, such as paid parental leave and childcare, and workplace flexibility are identified as very important. Shared domestic labour is also desired. Parents have the strongest expectations for care policy supports. Young men without children are least likely to factor these into future work trajectories, while young women do. However, data on women's plans for family formation, compared with men's, suggests that difficulties accessing vital care supports pose a risk to young women's ability to work, form families and care.